Вплив кріозахисних розчинів на метаболічну активність культури клітин Chlorococcum dіssectum та Dunaliella salina - Vozovyk, Krystyna; Chernobai, Nadiia; Kadnikova, Nataliya; Shevchenko, Nadiia (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2023)
Development of protocols for cryopreservation of microalgae Chlorococcum dissectum Korshikov and Dunaliella salina Teodoresco requires selection of eff ective cryoprotectants and their concentrations. One of the stages of choosing the optimal concentrations of cryoprotectants is determining the degree of toxicity for cells at the equilibration stage. Solutions of dimethyl sulfoxide, ethylene glycol, ethanol, glycerol (5–30%) and modified PVS1 and PVS2 (50 and 75%) were used in the research. The effect of cryoprotective compounds was determined by the resazurin reduction test. The least damaging effect on the Ch. dissectum cells was made by a 10% solution of glycerol. Treatment of the samples with ethanol and dimethyl sulfoxide solutions reduced metabolic activity by 31–33%, the ethylene glycol ones did by 50%. Incubation in 75% modified PVS1, 50 and 75% PVS2 solutions reduced the metabolic activity by more than half compared to the control. Ethanol was the most toxic cryoprotectant for D. salina cells. Exposure of cells to the solutions of dimethyl sulfoxide, ethylene glycol and glycerol reduced metabolic activity by 25%. Incubation of D. salina cells in PVS did not affect the studied index. Probl Cryobiol Cryomed 2023; 33(1):014–024